Enhancing Students' Motivation to Learn Chemistry - Yamit Sharaabi-Naor; Miri Kesner; Yael Shwartz (Universidade de Lisboa, 2014)
The interest, attitudes, and motivation of students towards science learning decreases over time, especially during the middle school years. In order to increase students' motivation to learn chemistry, a national program «Chemistry, Industry, and the Environment in the eyes of the individual and society» has been designed to integrate three main components: (1) a competition format; (2) a context-based approach, and (3) Project- ased learning (PBL). Literature supports the effectiveness of each approach in enhancing students' motivation. In this study we evaluated how the combination of these approaches influenced students' motivation to learn chemistry. In addition, we evaluated a similar project that took place in a single school. The comparison took into account students' characteristics regarding their intrinsic motivation to study chemistry as a subject in general and the nature of the project. We found that the national project increases students' motivation to learn chemistry, whereas a similar project that takes place in school does not have the same effect. Nevertheless, we noticed a small decline in interest throughout the project. Once again, this research provides additional evidence of the complexity of motivational processes.